Characterization and Molecular Mechanism of Peptide-Conjugated Gold Nanoparticle Inhibiting p53-HDM2 Interaction in Retinoblastoma - Sushma Kalmodia; Sowmya Parameswaran; Kalaivani Ganapathy; Wenrong Yang; Colin J. Barrow; Jagat R. Kanwar; Kislay Roy; Madavan Vasudevan; Kirti Kulkarni; Sailaja V. Elchuri; Subramanian Krishnakumar (Elsevier, 2017)
Inhibition of the interaction between p53 and HDM2 is an effective therapeutic strategy in cancers that harbor a wild-type p53 protein such as retinoblastoma (RB). Nanoparticle-based delivery of therapeutic molecules has been shown to be advantageous in localized delivery, including to the eye, by overcoming ocular barriers. In this study, we utilized biocompatible gold nanoparticles (GNPs) to deliver anti-HDM2 peptide to RB cells. Characterization studies suggested that GNP-HDM2 was stable in biologically relevant solvents and had optimal cellular internalization capability, the primary requirement of any therapeutic molecule. GNP-HDM2 treatment in RB cells in vitro suggested that they function by arresting RB cells at the G2M phase of the cell cycle and initiating apoptosis. Analysis of molecular changes in GNP-HDM2-treated cells by qRT-PCR and western blotting revealed that the p53 protein was upregulated; however, transactivation of its downstream targets was minimal, except for the PUMA-BCl2 and Bax axis. Global gene expression and in silico bioinformatic analysis of GNP-HDM2-treated cells suggested that upregulation of p53 might presumptively mediate apoptosis through the induction of p53-inducible miRNAs.